2011
DOI: 10.1038/cr.2011.103
|View full text |Cite
|
Sign up to set email alerts
|

The oncoprotein p28GANK establishes a positive feedback loop in β-catenin signaling

Abstract: p28GANK (also known as PSMD10 or gankyrin) is a novel oncoprotein that is highly expressed in hepatocellular carcinoma (HCC). Through its interaction with various proteins, p28GANK mediates the degradation of the tumor suppressor proteins Rb and p53. Although p53 was reported to downregulate β-catenin, whether p28 GANK is involved in the regulation of β-catenin remains uncertain. Here we report that both growth factors and Ras upregulate p28 GANK expression through the activation of the phosphoinositide 3-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…It has been previously reported that Gankyrin regulates transcription indirectly through NFkB and Wnt signaling pathways (2,17). To identify the transcriptional targets of Gankyrin, we conducted genome-wide screening using SW480 cells with Gankyrin knockdown on an Affymetrix gene expression array, which identified 937 genes that were differentially regulated by Gankyrin knockdown (1.5-fold, P < 0.05).…”
Section: Il-8 Signaling Pathway Is Regulated By Gankyrin In Crc Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that Gankyrin regulates transcription indirectly through NFkB and Wnt signaling pathways (2,17). To identify the transcriptional targets of Gankyrin, we conducted genome-wide screening using SW480 cells with Gankyrin knockdown on an Affymetrix gene expression array, which identified 937 genes that were differentially regulated by Gankyrin knockdown (1.5-fold, P < 0.05).…”
Section: Il-8 Signaling Pathway Is Regulated By Gankyrin In Crc Cellsmentioning
confidence: 99%
“…Overexpression of Gankyrin induces cyclin D1 protein expression in hepatic carcinoma (17). To test whether Gankyrin requires Cyclin D1 in promoting cell migration, we overexpressed Gankyrin in 3T3 fibroblast derived from Ccnd þ/þ and Ccnd À/À mice (30).…”
Section: Gankyrin Promotes Colorectal Cell Migration Through Targetinmentioning
confidence: 99%
See 1 more Smart Citation
“…101 Enforced expression of PSMD10 in hepatoma cells promoted dedifferentiation and also increased CD133 expression. 102 Regulation of PSMD10 transcription is activated by β-catenin and c-myc, 103 in addition to the general transcription panel members regulating other proteasome units expression, such as NRF2. 104 PSMD10 is a ubiquitin receptor and is involved in facilitation of degradation of both tumor suppressors p53 and Rb by the proteasome.…”
Section: Rbx1mentioning
confidence: 99%
“…Prof. Yan [10] reported the role of T cells in skin inflammation, Shao and Qian [11,12] have investigated the mechanisms of infections, Profs. Wang and Li have investigated the role of Wnt/β-catenin signaling in diseases [13,14]. Also researchers have made progress in elucidating mechanisms of development of tumorigenesis of lung cancer, breast cancer and colon cancer [13,15,16].…”
mentioning
confidence: 99%